Changes in infant respiratory pathogens pre-, during, and post-COVID-19 non-pharmacological interventions in Beijing - Tongying Han; Yajuan Wang; Di Zhang; Ying Li; Li Zhang; Jin Yan; Chi Li; Shengnan Yang; Litao Guo; Huijuan Yan (Italian Journal of Pediatrics)
Abstract Background To explore the effect of non-pharmacological interventions (NPIs) on respiratory pathogen profiles among hospitalized infants aged 0–3 months in Beijing during the coronavirus disease 2019 (COVID-19) pandemic. Methods Respiratory specimens were collected from 1,184 infants aged 0–3 months who were hospitalized for acute respiratory infection at the Children’s Hospital affiliated with the Capital Institute of Pediatrics from January 2018 to December 2023. The data were divided into three groups—the pre-epidemic (January 2018 to December 2019), epidemic prevention and control (January 2020 to December 2022), and post-epidemic (January 2023 to December 2023) groups—based on the outbreak of COVID-19 and the implementation and termination of NPIs. The specimens were tested for 14 respiratory pathogens, including influenza virus A (Flu A), influenza virus B, respiratory syncytial virus, parainfluenza virus (PIV), adenovirus (ADV), human metapneumovirus (HMPV), human bocavirus, human rhinovirus (HRV), coronavirus, Chlamydia trachomatis, Chlamydia pneumoniae (C.pn), Mycoplasma pneumoniae, Bordetella pertussis, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Results A total of 1,184 infants, including 649 males and 535 females, with acute respiratory infections were admitted. The positive detection rate for respiratory pathogens was 51.77% (n = 613). In 2023, the proportion of infants with respiratory infections after the epidemic was 19.4% (319/1646), the positive detection rate of respiratory pathogens was 68.3% (218/319), and the mixed infection detection rate of respiratory pathogens was 16.1% (35/218). Prior to the epidemic, these rates were 11.9% (431/3611), 37.1% (160/431), and 5.0% (8/160), respectively. During the epidemic prevention and control period, these rates significantly increased to 12.4% (434/3486), 54.1% (235/434), and 11.1% (26/235) (P < 0.05), respectively. Post-epidemic, the proportion of newborns testing positive for respiratory pathogens decreased, while the number of infants aged 29–90 days significantly increased. The proportion of admission weight and contact history with respiratory patients increased significantly compared to before and during the epidemic, with statistical significance (P < 0.05). After the epidemic, a total of 13 respiratory pathogens were detected throughout the year. There were statistically significant differences in the detection rates of Flu A, PIV, SARS-CoV-2, HRV, HMPV, ADV, and C.pn before, during, and after implementation of the NPIs during the COVID-19 epidemic (P < 0.05). Post-epidemic, the detection rates of Flu A, PIV, and SARS-CoV-2 were significantly higher than those before and during the epidemic (P < 0.017). The detection rates of HRV, HMPV, and ADV significantly increased after the epidemic compared to those before the epidemic (P < 0.017). Before the epidemic, the positivity rate of respiratory pathogens was high in the first and fourth quarters. After the termination of NPIs, the positive detection rate decreased in the first quarter but increased in the second, third, and fourth quarters, with a statistically significant difference (P < 0.05). Conclusion The implementation and lifting of COVID-19 NPIs have caused significant changes in the detection and seasonal distribution of respiratory pathogens in infants aged 0–3 months in Beijing. NPIs temporarily reduced the detection rate of respiratory pathogens in infants during the prevalence of COVID-19. Understanding the prevalence of respiratory pathogens before and after the epidemic is particularly important for the prevention and control of respiratory diseases in infants.